ANALISIS PENDAPATAN USAHATANI DAN EFISIENSI PEMASARAN KUNYIT (Curcuma domestica Val) - Kusnadi, Sidik; Novita, Ita; Miftah, Himmatul (JURNAL AGRIBISAINS, 2020)
Medicinal plants or biopharmaca plants are horticultural plants which are currently being developed to meet the needs of herbal medicinal raw materials that are experiencing high demand. One type of biopharmaca plant is turmeric (Curcuma domestica Val). Turmeric has many benefits as medicine and cooking spices. One of the turmeric producing regions is Sukabumi Regency, which is produced by Gapoktan Jaya Bakti farmers in Ciemas District. The objectives of this study are: (1) the income of Turmeric farming in Gapoktan Jaya Bakti, (2) the marketing channels (3) Analyzing the marketing efficiency of Turmeric. The research location is the area of Turmeric farmers who are members of Gapoktan Jaya Bakti in Sukabumi Regency, with the number of samples taken is 30 Turmeric farmers from 100 population of farmers in Gapoktan .The analysis used in this research is descriptive analysis and quantitative. The results showed that the income of Turmeric farmers on cash costs with an average land area of 4,269 m2 amounted to Rp1,477,511.11 and a total cost of Rp 1,373,877.78 with R / C of 1.20 and 1.18 for the total cost, this value shows the Turmeric farming in Gapoktan Jaya Bakti profitable. Tetrdapat 4 Turmeric marketing channels consisting of farmers, collector traders, village collector traders, wholesalers, retailers. The marketing function performed by each marketing institution is the exchange, physical and facility functions. Marketing efficiency can be seen in terms of farmers and traders, in terms of farmers marketing channel 4 is the most efficient channel and in terms of traders the most efficient marketing channel 1.Keywords : Medicinal Plants, Farm Income, Marketing Efficiency.